Postharvest oxidative behaviour of 1-methylcyclopropene treated Japanese plums (prunus salicina Lindell) during storage under controlled and modified atmospheres - Singh, S.; Singh, Zora (Elsevier, 2012)
Storage atmosphere composition is an important factor affecting potential storage life, susceptibility to physiological disorders and overall quality of fruit. We investigated the effects of controlled/modified atmospheres (CA/MA) on fruit quality, lipid peroxidation, and enzymatic and non-enzymatic antioxidative system in 1-MCP treated Japanese plums cv. ‘Blackamber’ during cold storage. Commercially mature fruit pretreated with 1-MCP (0.6µLL −1 for 12h) were stored for 5 and 8 weeks at 0–1 ◦C in different storage atmospheres, viz. normal air, 1% O2 and 3% CO2 (CA-1), 2.5% O2 and 3% CO2 (CA-2) and modified atmospheres (10% O2 and 3.8% CO2) generated through packaging in low density polyethylene bags. The results showed that storage under CA-1 and CA-2 was beneficial in delaying fruit ripening, retarding lipid peroxidation and reducing incidence and severity of chilling injury (CI) during 5 and 8 weeks of storage compared to normal air and MAP. The activities of enzymes involved in ascorbate–glutathione (AA–GSH) cycle were determined to explain the redox status of ascorbate and glutathione as influenced by storage atmospheres. CA conditions were favourable for the glutathione pool and the enzymes related to restoration of glutathione in the AA–GSH cycle, but the effects of CA on the ascorbate pool were not favourable.The data suggested that the enzymatic and non-enzymatic antioxidative systems were efficiently operating under low O2 atmospheres to scavenge reactive oxygen species produced in response to long-term chilling and gas stresses. CA conditions appeared to be limiting oxidative processes to some extent resulting in reduced oxidative damage. In conclusion, the development of CI, which is a manifestation of oxidative damage to the fruit tissue, can be significantly reduced through synergistic beneficial effects of CA and pretreatment with 1-MCP in Japanese plums.